Activated aggregation strategies to construct size‐increasing nanoparticles for cancer therapy. (30th August 2022) - Lu, Zhenni; Liu, Dongya; Wei, Peng; Yi, Tao
Abstract: The development of novel therapeutic strategies and modalities for tumors is still one of the important areas of current scientific research. Low permeability and short residence time of drugs in solid tumor areas are important reasons for the low efficiency of existing therapeutic strategies. Typically, nanoparticles with large size displayed enhanced residence time but low permeability. Therefore, to prolong the retention time of materials in solid tumors, size‐increasing strategies have been developed to directly generate large‐scale nanoparticles using small molecular compounds or increase the size of small nanoparticles in solid tumor areas. In this review, we summarize recently reported activatable aggregation systems that could be activated by cancer‐related substances for cancer therapy and classify them by the mechanisms that lead to aggregation. In the end, we propose some potential challenges briefly from the view of our opinion. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Present activated aggregation strategies of small‐sized nanoparticles or single molecular compounds to construct size‐increasing nanosystems, triggered by tumor microenvironment, or substrates of cancer cells for cancer therapy.